Gapless linear dispersion in Bi2Se3 nanoparticles for high-performance broadband photodetectors - Ghods, Soheil; Esfandiar, Ali; Choi, Jun Hui; Iraji zad, Azam; Josline, Mukkath Joseph; Kim, Sein; Lee, Jae Hyun (Materials Today Physics, 2023)
Topological insulators have demonstrated novel optoelectronic properties owing to their gapless linear dispersion and robust surface states. In this study, we implemented high-performance broadband photodetectors based on mixed-dimensional heterostructure of the topological insulator Bi2Se3 nanoparticles (NPs) with the semiconductor WSe2. Prominently, the Bi2Se3 NPs/WSe2 structure exhibited photoresponsivity of 22.17 A/W in the visible (Vis) wavelengths, and 5 A/W in the near-infrared (NIR) wavelengths and a fast response time of 40 μs. In comparison with typical semiconducting PbS NPs/WSe2 structure, we confirmed that the enhancement in the photoresponsivity, response time, and broadband photoresponse of the Bi2Se3 NPs/WSe2 structure can be attributed to the gapless behavior in surface states of topological insulator materials. Numerical simulations also confirmed a dramatic increase in the interfacial electric field by two orders of magnitude, resulting from the surface states in topological insulator NPs. The observed experimental results and the proposed mechanism pave the way for the emergence of efficient optoelectronic devices based on topological insulator materials.
Keywords: Fast response time; Insulator materials; Linear dispersion; Near-infrared wavelength; Optoelectronics property; Performance; Photoresponses; Photoresponsivity; Topological insulators; Visible wavelengths; Bismuth selenide; Nanoparticles; Photodetector; Topological insulator; Tungsten diselenide